Analisis Praktik Live Selling Wish Color di TikTok Prespektif Marketing Syariah - Karina Widya Andari (Comprehensive Journal of Islamic Studies, 2025)
The development of digital technology has transformed the marketing landscape, including the emergence of wish color live selling practices on the TikTok Shop platform that incorporate gamification elements in marketing strategies. This research aims to analyze the compatibility of wish color live selling practices with Islamic marketing principles. The research method employs a descriptive qualitative approach using library research techniques through the collection of documents, books, and articles related to Islamic marketing and wish color live selling. The research findings indicate that wish color live selling practices can align with Islamic marketing principles if they fulfill four main characteristics: Religious (Rabbaniyah), Ethical (Akhlakiyyah), Realistic (Al-Wai'iyyah), and Humanistic (Al-Insaniyyah), and implement prophetic values including shiddiq (honesty), fathanah (intelligence), tabligh (communicative), and amanah (trustworthiness). This practice is acceptable as long as sellers maintain transparency, provide minimum product guarantees for consumers (minimum take-home), do not harm either party, take responsibility for replacing defective products, and conduct effective communication. Nevertheless, potential risks such as information ambiguity, promotional manipulation, and impulses toward impulsive buying must still be monitored. This research concludes that digital marketing innovations such as wish color can integrate with Islamic values as long as they are conducted with principles of justice, honesty, consumer protection, and provide benefits for all parties without containing elements of deception or exploitation.